Developing IT Strategic Plan for Mangrove Conservation Using TOGAF ADM: A Case Study of the M4CR Loan Project - Putu Raditya Astika Putra; Dana Indra Sensuse; Raden Trimanadi (Information System Study Program, Faculty of Engineering and Vocational, Undiksha, 2026)
The Mangrove for Coastal Resilience (M4CR) Loan Project is a national initiative supported by a USD 400 million World Bank loan targeting the rehabilitation of 600,000 hectares of degraded mangroves in Indonesia. Loan disbursement is governed by Performance-Based Conditions (PBC), demanding a reliable, integrated ICT system. However, the project suffers from fragmented ICT development, absence of a strategic plan, and post-institutional transition challenges following the dissolution of BRGM in 2024. This study aims to develop an ICT Master Plan (RITIK) for M4CR using the TOGAF Architecture Development Method (ADM). A qualitative interpretive approach combining case study and action research was employed. Data was collected through in-depth interviews with three key informants (PPK, IT Expert, IT Assistant), observation, and document review. TOGAF ADM was applied from the Preliminary Phase through Opportunities, Solutions, and Migration Planning (Phases E–F), with ArchiMate 3.2 as the modeling notation. Results include: (1) a five-module integrated IS architecture (SI_DMPM, SI_KONTRAK, SI_OPERASIONAL, SI_EKSEKUTIF, SI_PENGETAHUAN) built on an open-source infrastructure stack (PostgreSQL/PostGIS, GeoServer, containerization); (2) a technology architecture shifting from fragmented SaaS dependency to a centralized, organization-owned server; and (3) a four-phase technical implementation roadmap (2026–2027) within a broader 2026–2030 ICT strategic planning horizon designed to ensure post-project governance continuity validated through internal FGD. The RITIK provides strategic guidance for ICT governance continuity across institutional transitions and PBC target acceleration.